UTILIZING SIGN LANGUAGE GESTURES FOR GESTURE-BASED INTERACTION: A USABILITY EVALUATION STUDY - Son, Minseok; Park, Woojin; Jung, Jaemoon; Hwang, Dongwook; Park, Jungmin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
Utilizing gestures of major sign languages (signs) forgesture-based interaction seems to be anappealing idea as it has some obvious advantages, including: reduced time and cost for gesture vocabulary design, immediate accommodation of existing sign language users and supporting universal design and equalityby design. However, it is not wellunderstood whether or not sign language gestures are indeed adequate forgesture-based interaction, especially in terms of usability. As an initial effort to enhance ourunderstanding of the usability of sign language gestures, the current study evaluated Korean Sign Language (KSL) gestures employing threeusability criteria: intuitiveness, preference and physicalstress. A set of 18 commandsfor manipulating objects in virtualworlds was determined. Then, gestures for thecommands were designed using two designmethods: the sign language method and the user designmethod. The sign language method consisted of simplyidentifying the KSL gestures corresponding to the commands. The user design method involved having userrepresentatives freely design gestures for the commands. A group of evaluators evaluated the resultingsign language and user-designed gestures in intuitiveness and preferencethrough subjective ratings. Physicalstresses of the gestures were quantified using an index developed based on RapidUpper Limb Assessment. The usabilityscores of the KSL gestures were compared with those of the user-designedgestures for relative evaluation. Data analyses indicated that overall, the use of theKSL gestures cannot be regarded as an excellent design strategy when viewedstrictly from a usability standpoint, and the user-design approach would likelyproduce more usable gestures than the sign language approach if designoptimization is performed using a large set of user-designed gestures. Based on the study findings, some gesturevocabulary design strategies utilizing sign languagegestures are discussed. The study findings may inform future gesturevocabulary design efforts.